THE PERCEPTIONS OF LOCAL ACTORS ON BIOGAS IN WEST OF PARANÁ - Strassburg, Udo (2020)
This paper aims to analyze the perceptions of local actors about biogas in the West of Paraná region, Brazil. The analysis has been done through the Discourse of the Collective Subject (DCS) technique. The theoretical framework is based on the concepts of institutions and organizations. The main results of the research indicate that the agro-industrial system of biogas in the West of Paraná has good perspectives in the production, transformation and commercialization of biogas. It was pointed out that there are great challenges in biogas, such as: lack of public policies, the dispersion of unity among biogas producers, few investments in technology and low tax incentives. The Biogas SAG of Western Paraná is only in its early stages, but has great potential to operate in this area, due to the large pig breeding stock. It could be an important agent for the production of renewable energy. What is lacking are strong institutions, social and political articulation so that the economy of this sector can be strong and thriving, taking advantage of waste that has a great potential for pollution to turn into renewable energy, contributing to the energy sustainability of our country.